Study of the influence of the structure of the alcohol on vapor pressures and osmotic coefficients of binary mixtures alcohol + 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide at T = 323.15 K - Noélia Calvar (2012)
The osmotic and activity coefficients and vapor pressures of binary mixtures containing thealcohols 1-propanol, 2-propanol, 1-butanol, 2-butanol and 1-pentanol and the ionic liquid 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, C6MimNTf2, were determined at T = 323.15 Kusing the vapor pressure osmometry technique. The experimental osmotic coefficients were correlatedusing the Extended Pitzer model of Archer and the MNRTL model, obtaining standard deviations lowerthan 0.020 and 0.049, respectively. The mean molal activity coefficients and the excess Gibbs free energyfor the studied mixtures were calculated from the parameters of the Extended Pitzer model of Archer.Besides the effect of the alkyl-chain of the alcohol and the position of the alcohol group, the effect of thealkyl-side chain of the cation of the ionic liquid can be assessed comparing the experimental results withthose previously obtained for imidazolium bis(trifluoromethylsulfonyl)imide ionic liquids with differentalkyl-side chain lengths.